CONSTITUTIONAL COURT DECISION NUMBER 6/PUU-XIX/2021 CONCERNING THE REVIEW OF THE JOB CREATION LAW SIYASAH TASYRI'IYYAH PERSPECTIVE - Fatmah, Fatmah (IBN KHALDUN BOGOR, 2023)
The decision of the Constitutional Court Number 6/PUU-XIX/2021 states that Law Number 11 of 2020 Concerning Job Creation is unconstitutional because it does not fulfill the element of public participation, is not following the technique of drafting laws, and has changed even though it has been agreed in the plenary session of the DPR when it will be ratified. However, the decision of the Constitutional Court still draws protests from the public because it does not firmly state that Law Number 11 of 2020 Concerning Job Creation is unconstitutional, so it must be completely and completely annulled. Therefore, this research will start the analysis of views siyasah tasyri'iyyah and the perspective of law science in Indonesia This type of research is libraryresearch. In this case, the researcher is dealing with text or data that is directly usable which can be found in the library. The results of this study concluded that the view of siyasah tasyri'iyyah and the science of legislation is true the first principle of siyasah tasyri'iyyah simplify and simplify, but this must be seen holistically from the point of view of the principle of gradually,in line with human benefit, realizing equitable justice. The Job Creation Law cannot be said to be ideal, so it needs improvement. Even if examined from a philosophical, juridical and sociological basis, the Job Creation Law did not fulfill aspects of public participation, had no legal basis for making it at the time the MK Decision was issued and did not reflect the basic needs of society.